Adaptations on the edge: post-secular placemaking and the adaptive reuse of worship spaces in Newfoundland. (12th February 2022) - Lynch, Nicholas; LeDrew, Rebecca
ABSTRACT: The closure and reuse of worship spaces is a growing global phenomenon. In recent decades, societal, demographic, financial and other pressures have led to the shuttering of vast numbers of worship spaces throughout North America, Europe and parts of Asia. While most research focuses on the reuse of worship spaces in large cities, across Canada there exists countless small cities and rural settlements that are contending with closure and finding innovative ways to reuse these important social, cultural and material assets. Through site visits and in-depth interviews, this paper investigates the adaptive reuse of two important worship spaces in Newfoundland's Avalon Peninsula, an important yet peripheral space in Atlantic Canada. In particular, we explore, first, how a local historic church in the City of St. John's employed adaptive reuse to revitalize religious mission and develop a social enterprise to deliver community services. Second, we explore how local entrepreneurs in a rural area adapted an historic convent to a globally-inspired gastropub and B&B. Together, these case studies demonstrate the evolving geographies of the postsecular and the complex, and sometimes contentious, ways that adaptive reuse not only frames how the secular and the religious are valued, but also how it reimagines socio-cultural space along the edge.